2019
DOI: 10.1021/acs.biochem.9b00295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of V83G and I81A Substitutions to Human Cytochrome c on Acid Unfolding and Peroxidase Activity below a Neutral pH

Abstract: Mitochondrial cytochrome c is a highly conserved protein in eukaryotes. Certain functions of cytochrome c have been tuned during evolution. For instance, the intrinsic peroxidase activity of human cytochrome c is much lower than that of the yeast counterpart. Structural studies on K72A yeast iso-1-cytochrome c [McClelland, L. J., et al. (2014) Proc. Natl. Acad. Sci. USA, 111, 6648–6653] revealed that residues 81 and 83 in Ω-loop D (residues 70–85) may be gatekeeper residues for the peroxidase activity linked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 79 publications
6
27
0
Order By: Relevance
“…However, we have recently reported kinetic data for the V83G and I81A variants of Hu Cytc, which we fit assuming two slow phases. 64 Values of pK H for both the k obs,1 and k obs,2 phases were within the range of 10.7−11.2 for kinetic data fit with two slow phases for these variants (Table 6). 64 As for the G41S and Y48H variants, the increased access to alternate conformers for the A51V variant appears to result from a decrease in the pK H of the triggering deprotonation.…”
Section: ■ Experimental Methodsmentioning
confidence: 61%
See 2 more Smart Citations
“…However, we have recently reported kinetic data for the V83G and I81A variants of Hu Cytc, which we fit assuming two slow phases. 64 Values of pK H for both the k obs,1 and k obs,2 phases were within the range of 10.7−11.2 for kinetic data fit with two slow phases for these variants (Table 6). 64 As for the G41S and Y48H variants, the increased access to alternate conformers for the A51V variant appears to result from a decrease in the pK H of the triggering deprotonation.…”
Section: ■ Experimental Methodsmentioning
confidence: 61%
“…The I81A variant of Hu Cytc also shows enhanced kinetic accessibility of only one of the two kinetically distinguishable alkaline conformers in 0.1 M NaCl. 64 In this case, pK H for k obs,1 is unchanged, whereas pK C is more favorable because k f is larger and k b is smaller (Table 6). Notably, k f and k b derived from k obs,1 for the V83G variant are similar to those of the A51V variant, yielding a similar less favorable pK C for these two variants (Table 6).…”
Section: ■ Experimental Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that mutations in the Ω-loop D (70–85) such as K72A, P76C, K79G/M80X, I81A, F82K, and V83G may alter the heme crevice dynamics and ligand-binding properties. 19 , 32 , 40 42 …”
Section: Resultsmentioning
confidence: 99%
“…The strong correlation between the peroxidase activity and acidic pH indicates that Ile81 is a peroxidase trigger in h Cyt c . It is worth mentioning that the peroxidase activity of the I81A variant ( k cat = 0.96 ± 0.01 s –1 ) 32 is 6-fold higher than that of the I81N ( k cat = 0.16 ± 0.01 s –1 ) and 8.7-fold higher than that of the WT ( k cat = 0.11 ± 0.01 s –1 ) at neutral pH, and thus the I81A mutation may not be allowed naturally.…”
Section: Resultsmentioning
confidence: 99%